Persepsi Peserta Didik Terhadap Larangan Merokok di SMP Negeri 6 Kabupaten Banyuasin Sumatera Selatan - Zhafirah, Annisa Indah; Ningsih, Vinna Rahayu; Ridwan, Muhammad (UI Scholars Hub, 2024)
Background: The smoking ban policy in Indonesia has not been fully complied with by the public, including the smoking ban policy in schools. One of the factors contributing to the lack of compliance with the smoking ban policy in schools is the perception regarding the smoking ban. This research aims to understand students' perceptions regarding the smoking ban in the school environment. Method: this research uses a qualitative approach with a case study. The subjects of this research consisted of 43 individuals, including 13 informants for in-depth interviews, namely 5 students, 1 principal, 1 guidance and counseling teacher, 6 parents of students, and 3 Focus Group Discussion (FGD) groups with 10 student participants. Data management with Nvivo 12 Pro software. Result: The school has provided education to students through posters and counseling. Efforts to enforce the smoking ban have been implemented by the school, but they have not yet raised awareness among students about not smoking. Knowledge of the smoking ban in the school environment is known to students when they first enter middle school; students feel curious about cigarettes and find smoking enjoyable at school. Conclusion: Students' perceptions of the smoking ban in ninth grade have a better understanding than those in eighth grade. Students perceive cigarettes as a pleasure and have a curiosity to try smoking.